Gender Differences in Written Mathematical Communication: An Analysis of Students’ Problem-Solving Processes - Pieter Zakarias Tupamahu; Christina M. Laamena; Nelma Dortje Lethulur ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
In mathematics education, written mathematical communication (WMC) is crucial for students to articulate problem-solving processes, yet gender differences and underlying weaknesses in high school contexts remain underexplored, particularly in linear programming tasks. This study aims to analyze the WMC of eleventh-grade high school students in solving linear programming problems from a gender perspective. A sequential explanatory mixed-methods approach was employed with 44 students from Ambon City high schools. Quantitative data from WMC assessments were analyzed using descriptive statistics and multiple linear regression to evaluate overall performance, indicator dominance (accuracy vs. completeness), and gender effects. Six participants were then purposively selected for semi-structured interviews based on ability levels (high, medium, low) and gender, providing qualitative insights into problem-solving phases. Results showed low overall WMC (male dominance: 27.4%; female: 29.6%), with accuracy (M = 53.54–54.5%) outperforming completeness (M = 32.32–32.83%). Regression analysis indicated no significant gender effect. Interviews revealed systematic weaknesses in the entry phase (contextual data interpretation), attack phase (symbolic-graphic representation), and review phase (reflective evaluation).  These findings highlight that WMC depends not only on computational skills but also on metacognitive abilities for coherent argumentation. Teachers should implement reflection-based learning to foster contextual writing, comprehensive visual labeling, and evaluative conclusions.